Retinal oxygen saturation is an independent risk factor for the severity of diabetic retinopathy. Issue 8 (18th October 2018) - Bek, Toke; Stefánsson, Einar; Hardarson, Sveinn Hákon
Abstract : Background: The oxygen saturation in larger retinal vessels has been shown to increase with increasing diabetic retinopathy (DR) grade and to help predict the effect of antivascular endothelial growth factor treatment in patients with diabetic maculopathy. However, it is unknown to what extent the increased oxygen saturation co-varies with other risk factors and whether it is an independent risk factor for the severity of DR. Methods: Seven hundred and twenty-two successive patients referred for specialist evaluation of diabetic retinopathy including retinal oximetry were studied. Multiple regression analysis was used to investigate whether oxygen saturation in the larger retinal arterioles and venules contributed to the severity of diabetic retinopathy, independently of gender, age, diabetes duration, diabetes type, body mass index, blood pressure, haemoglobin A1c, visual acuity and central retinal thickness. Results: The included parameters could explain less than 15% of the variation in retinopathy grade. Approximately, one-third of the explained variation was related to the retinal oxygen saturation. Conclusions: Prospective studies are needed to evaluate whether retinal oxygen saturation is predictive for the development of diabetic retinopathy and how it interacts with other biomarkers and risk factors over time.